2005
DOI: 10.1021/ja0442567
|View full text |Cite
|
Sign up to set email alerts
|

A Photoinducible β-Hairpin

Abstract: A photochromic azobenzene linker was incorporated as a turn element into an amino acid sequence known to fold into a beta-hairpin structure in aqueous solution. Oligomer formation when the linker was in its thermodynamically favored trans form prohibited structure determination. Light-induced conformational change of the linker to the cis form led to the formation of monomers which exhibited a well-defined beta-hairpin structure as determined by (1)H NMR. The rate of the light-induced cis-to-trans isomerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 52 publications
1
127
0
2
Order By: Relevance
“…56,57 In addition, Hilvert has found that unlike D-ProGly type II′ turns, the type I′ reverse turns generated by cis-AMPP are more mobile and the backbone of each proximal strand of the hairpin are flipped 180°reversing the hydrogen bonding pattern relative to type II′ turns. 38 Because hairpin stability is dictated by multiple factors, including hydrogen bonding, secondary structure propensities of residues in the strands, and side chain interactions, these differences could have a profound impact on the stability of the resultant conformations and impede transition to cross-β fibrils. 38 If cis-AMPP does form a type I′ turn in the context of peptide 2, it may represent a non-native and highly stable β-hairpin conformation that precludes rotation into the nonhairpin turn found in Aβ oligomers and fibrils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56,57 In addition, Hilvert has found that unlike D-ProGly type II′ turns, the type I′ reverse turns generated by cis-AMPP are more mobile and the backbone of each proximal strand of the hairpin are flipped 180°reversing the hydrogen bonding pattern relative to type II′ turns. 38 Because hairpin stability is dictated by multiple factors, including hydrogen bonding, secondary structure propensities of residues in the strands, and side chain interactions, these differences could have a profound impact on the stability of the resultant conformations and impede transition to cross-β fibrils. 38 If cis-AMPP does form a type I′ turn in the context of peptide 2, it may represent a non-native and highly stable β-hairpin conformation that precludes rotation into the nonhairpin turn found in Aβ oligomers and fibrils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6, 10 To reliably access glucagon‐like peptide‐1 receptor (GLP‐1R) photoactivation through geometric alterations to ligand structure, an azobenzene photoswitch comprising the amino acid [3‐(3‐aminomethyl)phenylazo]phenylacetic acid (AMPP)9b, 11 was incorporated into liraglutide. To minimize disruption to helix folding, AMPP was inserted as a bridge between the two α‐helices of liraglutide (PDB ID: 4apd; Figure 1 a), replacing amino acids 22 G‐ 23 Q, to obtain LirAzo by solid‐phase peptide synthesis (Figure 1 c and Table S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…We and others (8)(9)(10) have recently focused on the design of photocontrolled ␤-hairpin peptides. To enable an ultrafast initiation of ␤-hairpin folding and unfolding the azobenzene derivative 3-(3-aminomethylphenylazo)phenylacetic acid (AMPP) was used as a reversible light switch (8,10), which, in the cis isomeric state, acts as ␤-turn mimetic (see Fig. 1A).…”
mentioning
confidence: 99%